Determination of trap density-of-states distribution of nitrogen-doped ultrananocrystalline diamond/hydrogenated amorphous carbon composite films. (June 2021) - Shaban, Mahmoud
Abstract: Thin films comprising nitrogen-doped ultrananocrystalline diamond/hydrogenated amorphous-carbon (UNCD/a-C:H) composite films were experimentally investigated. The prepared films were grown on Si substrates by the coaxial arc plasma deposition method. They were characterized by temperature-dependent capacitance-frequency measurements in the temperature and frequency ranges of 300–400 K and 50 kHz–2 MHz, respectively. The energy distribution of trap density of states in the films was extracted using a simple technique utilizing the measured capacitance-frequency characteristics. In the measured temperature range, the energy-distributed traps exhibited Gaussian-distributed states with peak values lie in the range: 2.84 × 10 16 –2.73 × 10 17 eV –1 cm –3 and centered at energies of 120–233 meV below the conduction band. These states are generated due to a large amount of sp 2 -C and π-bond states, localized in GBs of the UNCD/a-C:H film. The attained defect parameters are accommodating to understand basic electrical properties of UNCD/a-C:H composite and can be adopted to suppress defects in the UNCD-based materials.